A New Electric Vehicle Charging-Ordered Control Model Based On Time-Divided Algorithm. Issue 5 (March 2019) - He, Jialin; Qi, Jiajin; Zheng, Zhengxian; Xu, Yu; Shan, Leijing; Yan, Xingping
Abstract: This paper proposed a novel plug-in electric vehicle charging-ordered based on time-sharing control algorithm, the algorithm under the condition of meet the demand of the electric car charging users, by charging stations operating income maximization as the goal, uses the monte carlo simulation method to simulate the user charge needs to transport characteristics of the electric car users conditional probability analysis, and then through the way of peak stagger, established the mathematical model in orderly electric vehicle charging stations. Research results show that the dynamic grid through time-sharing control and time-sharing electricity two kinds of incentive, orderly charging control method can significantly improve the economics of electric vehicle charging station distribution network, reduce the voltage stress of distribution network, and has high computational efficiency.